Hypoglycaemia in adrenal insufficiency - Lee, Shien Chen; Baranowski, Elizabeth S.; Sakremath, Rajesh; Saraff, Vrinda; Mohamed, Zainaba (Frontiers in Endocrinology, 2023)
Adrenal insufficiency encompasses a group of congenital and acquired disorders that lead to inadequate steroid production by the adrenal glands, mainly glucocorticoids, mineralocorticoids and androgens. These may be associated with other hormone deficiencies. Adrenal insufficiency may be primary, affecting the adrenal gland's ability to produce cortisol directly; secondary, affecting the pituitary gland's ability to produce adrenocorticotrophic hormone (ACTH); or tertiary, affecting corticotrophin-releasing hormone (CRH) production at the level of the hypothalamus. Congenital causes of adrenal insufficiency include the subtypes of Congenital Adrenal Hyperplasia, Adrenal Hypoplasia, genetic causes of Isolated ACTH deficiency or Combined Pituitary Hormone Deficiencies, usually caused by mutations in essential transcription factors. The most commonly inherited primary cause of adrenal insufficiency is Congenital Adrenal Hyperplasia due to 21-hydroxylase deficiency; with the classical form affecting 1 in 10,000 to 15,000 cases per year. Acquired causes of adrenal insufficiency can be subtyped into autoimmune (Addison's Disease), traumatic (including haemorrhage or infarction), infective (e.g. Tuberculosis), infiltrative (e.g. neuroblastoma) and iatrogenic. Iatrogenic acquired causes include the use of prolonged exogenous steroids and post-surgical causes, such as the excision of a hypothalamic-pituitary tumour or adrenalectomy.Clinical features of adrenal insufficiency vary with age and with aetiology. They are often non-specific and may sometimes become apparent only in times of illness. Features range from those related to hypoglycaemia such as drowsiness, collapse, jitteriness, hypothermia and seizures. Features may also include signs of hypotension such as significant electrolyte imbalances and shock. Recognition of hypoglycaemia as a symptom of adrenal insufficiency is important to prevent treatable causes of sudden deaths. Cortisol has a key role in glucose homeostasis, particularly in the counter-regulatory mechanisms to prevent hypoglycaemia in times of biological stress. Affected neonates particularly appear susceptible to the compromise of these counter-regulatory mechanisms but it is recognised that affected older children and adults remain at risk of hypoglycaemia.